Nickel-rich positive electrode material and preparation method thereof, positive electrode plate, lithium ion battery and electric equipment
By adopting yin and yang ion coupling co -doping strategies in nickel -rich positive materials to improve the proportion of atomic vacancy and adjustment of NI elements during the sintering process, the problem of cycle stability and thermal stability of nickel -rich positive material in existing technologies will deteriorate. Realize higher capacity and more stable electrochemical properties.
Patent Information
- Application Number
- CN202411866113.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
As the Ni content increases, the cycle stability and thermal stability of the existing nickel-rich layered oxide positive electrode materials are deteriorated.
Using yin and yang ion coupling co -doping strategies, kernels are mixed with N elements and cationic elements, the cover layer includes N elements and cationic elements. By regulating the proportion of yin and yang ion income, improve the atomic vacancy during the sintering process, and adjust the proportion of NI elements. Increase the proportion of NI3+, and by introducing cation doping, regulating particle density and growth consistency, stabilizing the crystal cell structure.
It improves the capacity, lithium -ion diffusion coefficient and dynamic performance of nickel -rich positive materials, slow down the extent of the stress of the internal volume stress of the material, and enhance the electrochemical performance and interface stability.
Smart Images

Figure CN119340379A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a nickel-rich positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery, and electrical equipment. Background Art
[0002] The positive electrode material of lithium-ion batteries has a crucial impact on their energy density, thermal stability, service life, and cost. Nickel-rich layered oxides such as LiNi x Co y Mn 1-x-y O2、LiNi x Co y Al 1-x-y O2 (x ≥ 0.8) has attracted widespread attention due to its reasonable cost and high energy density. Increasing the proportion of Ni is currently the most effective way to further increase battery energy density and reduce production costs. However, the cycling stability and thermal stability of the positive electrode material of nickel-rich layered oxides will also deteriorate as the Ni content increases. Summary of the invention
[0003] The purpose of the present application is to provide a nickel-rich positive electrode material and a preparation method thereof, a positive electrode plate, a lithium-ion battery, and electrical equipment, aiming to solve the problem that the cyclic stability and thermal stability of the existing nickel-rich layered oxide positive electrode material will deteriorate as the Ni content increases.
[0004] To achieve the above objectives, the present application provides a nickel-rich positive electrode material, including a core and a coating layer covering the core, the core is doped with N element and cationic element, and the coating layer includes N element and cationic element; the chemical formula of the nickel-rich positive electrode material is LiNi x Co y Mn z Al 1-x-y-z C c D d N n O2; wherein, 0.80≤x≤0.95, 0≤y≤0.10, 0≤z≤0.10, C is the cationic element doped in the core, 0.10≤c≤0.30, D is the cationic element in the coating layer, 0.10≤d≤0.20, and n≤0.45.
[0005] In some embodiments, the cationic element doped with the core includes at least one of Zr, Sr, Y, Al, B, Mg, Nb, and Mo; The cationic element in the coating layer includes at least one of Al, W, Ti, Ce, Co, Ta, and Er.
[0006] In some embodiments, at least one of the following conditions is met: (1) The thickness of the coating layer is 1~3nm; (2) The D50 of nickel-rich cathode materials is 9.0 μm~13.5 μm; (3) The specific surface area of nickel-rich positive electrode materials is 0.25~0.80m 2 / g; (4) The tap density of nickel-rich positive electrode material is ≥2.2g / cm 3 ; Optionally, the tap density of the nickel-rich positive electrode material is 2.2~2.8g / cm 3 ; (5) The 003 / 104 diffraction peak intensity ratio in the XRD characteristic peak of the nickel-rich positive electrode material is ≥1.30; Optionally, the 003 / 104 diffraction peak intensity ratio in the XRD characteristic peak of the nickel-rich positive electrode material is 1.30-1.45; (6) The nickel-rich cathode material is a spherical secondary particle composed of stacked primary particles; (7) When condition (6) is met, the length of the primary particle is 300~500nm; (8) When condition (6) is met, the aspect ratio of the primary particles is between 1.5 and 3.0.
[0007] The present application also provides a method for preparing the above-mentioned nickel-rich positive electrode material, comprising: Performing a first mixing of a nickel-rich positive electrode material precursor and a lithium source, and adding a first two-phase coupling initiator during the first mixing process to obtain a first mixture; Performing a first sintering on the first mixture to obtain a material to be coated; Performing a second mixing of the material to be coated, and adding a second dual-phase coupling initiator during the second mixing process to obtain a second mixture; The second mixture is subjected to a second sintering to obtain a nickel-rich positive electrode material; Wherein, the first two-phase coupling initiator and the second two-phase coupling initiator both include anion elements and cation elements, and the anion element is N.
[0008] In some embodiments, a nickel-rich cathode material precursor and a lithium source are first mixed, and a first dual-phase coupling initiator is added during the first mixing process, including: During the first mixing process of the nickel-rich positive electrode material precursor and the lithium source, a first two-phase coupling initiator after ultrasonic atomization is sprayed, and microwave drying is performed to obtain a first mixture; And / or, subjecting the material to be coated to a second mixing process and adding a second dual-phase coupling initiator during the second mixing process, comprising: During the second mixing process of the material to be coated, the second dual-phase coupling initiator after ultrasonic atomization is sprayed in, and microwave drying is performed to obtain a second mixture.
[0009] In some embodiments, the first mixing and the second mixing processes both include: a first stage, a second stage, and a third stage in which the mixing speed increases sequentially; and at least one of the following conditions is met: A. The speed of the first stage is 50-400r / min, and the time is 1-5min; B. The speed of the second stage is 100-600r / min, and the time is 2-10min; C. The speed of the third stage is 400-1000r / min, and the time is 10-20min; D. The first two-phase coupling initiator after ultrasonic atomization and the second two-phase coupling initiator after ultrasonic atomization are both sprayed in the second stage; E. The injection rate of the first two-phase coupling initiator after ultrasonic atomization and the second two-phase coupling initiator after ultrasonic atomization is 10-50 mL / min; F. Microwave drying is carried out in the third stage; G. The power of microwave drying is 8-15kW and the temperature is 50-80℃.
[0010] In some embodiments, at least one of the following conditions is met: A. Based on the mass of the nickel-rich positive electrode material precursor, the amount of the first dual-phase coupling initiator added is 1000-3000ppm; B. Based on the mass of the material to be coated, the amount of the second dual-phase coupling initiator added is 1000-2000ppm; C. The first two-phase coupled initiator and the second two-phase coupled initiator are both secondary particles composed of primary particles, the particle size of the primary particles is ≤30nm, and the particle size of the secondary particles is 1μm~3μm; D. The cationic element of the first dual-phase coupling initiator includes at least one of Zr, Sr, Y, Al, B, Mg, Nb, and Mo; the cationic element of the second dual-phase coupling initiator includes at least one of Al, W, Ti, Ce, Co, Ta, and Er; E. The first sintering comprises: continuously introducing oxygen, heating from room temperature to 450°C at a heating rate of 5°C / min and keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 1°C / min and keeping the temperature for 2 hours, then heating to 700-800°C at a heating rate of 2°C / min and keeping the temperature for 10-15 hours; F. The second sintering includes: heating from room temperature to 500-700°C at a heating rate of 2°C / min and keeping the temperature for 6-12h; G. The chemical formula of the nickel-rich positive electrode material precursor is: Ni x Co y Mnz Al 1-x-y-z (OH)2, where 0.80≤x≤0.95, 0≤y≤0.10, 0≤z≤0.10; H. The particle size D50 of the lithium source is 1 μm to 5 μm; I. The lithium source is selected from any one of LiOH, Li2CO3, CH3COOLi, and Li2C2O4.
[0011] The present application also provides a positive electrode plate, comprising the above-mentioned nickel-rich positive electrode material.
[0012] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0013] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0014] Compared with the prior art, the beneficial effects of this application include: The nickel-rich positive electrode material provided in the present application adopts an anion-cation coupling co-doping strategy. The doping of N element in the anion can improve the atomic vacancies generated during the sintering process, and rearrange the charges in the unit cell structure by increasing the vacancy concentration of the electron position in the energy level band gap, adjusting the ratio of Ni elements with different valence states in the nickel-rich positive electrode material, and improving Ni 3+ The proportion of Ni 2+ By increasing the spacing between the unit cell layers, the primary particles can be regulated to increase the particle density and growth consistency, thus broadening the Li + Transmission channel, stabilize the cell structure, increase Ni 2+ The migration energy barrier and the escape energy barrier of O2 can improve the lithium ion diffusion coefficient and kinetic performance, and slow down the drastic change of volume stress inside the primary particles of the material. In addition, after the introduction of cations into the material, the internal charge can be balanced by adjusting the ratio of anions and cations, and the Ni 2+ / Ni 3+ ratio, so that the material can achieve the optimal Li / Ni mixed state and improve the electrochemical performance of the material.
[0015] The nickel-rich positive electrode material provided in the present application constructs a high-entropy material surface-low-entropy material interior dual-phase state by co-coating of N elements and cationic metal elements on the surface, utilizes the high-entropy shielding effect to reduce the dissolution of transition metals, inhibits the catalytic effect of transition metals on the electrolyte, improves the structural stability of the CEI film, slows down the epitaxial growth of the CEI film, stabilizes the median voltage, and effectively reduces the interface impedance of the positive electrode material.
[0016] In order to avoid the problem of poor kinetics in gas-solid two-phase reactions, the preparation method of the nickel-rich positive electrode material provided in the present application provides a strategy of ultrasonic atomization and microwave radiation-assisted drying to introduce a two-phase coupling initiator into the interior and surface of the primary particles of the positive electrode material in the form of liquid-solid dispersion. The low-entropy phase elements inside are evenly distributed, and the orientation of the primary particles is consistent, which greatly alleviates the damage of the volume anisotropic stress to the interior of the material. The high-entropy phase limits the surface reconstruction, slows down the dissolution of elements and the erosion of harmful substances, and utilizes two-phase coupling to improve the various properties of the nickel-rich positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0018] Figure 1 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 1; Figure 2 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 2; Figure 3 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 3; Figure 4 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 4; Figure 5 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 5; Figure 6 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 6; Figure 7 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 7; Figure 8 This is a scanning electron microscope image of the nickel-rich positive electrode material of Example 8; Fig. 9 This is a scanning electron microscope image of the nickel-rich positive electrode material of Comparative Example 1; Fig.10 This is a scanning electron microscope image of the nickel-rich positive electrode material of Comparative Example 2; Fig.11 This is a scanning electron microscope image of the nickel-rich positive electrode material of Comparative Example 3; Fig.12 This is a scanning electron microscope image of the nickel-rich positive electrode material of Comparative Example 4; Fig.13 The first electrochemical charge-discharge curves of Example 4, Example 7 and Comparative Examples 1 to 4; Fig.14 Schematic diagram of the process of preparing the nickel-rich positive electrode material of the present application. DETAILED DESCRIPTION
[0019] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0020] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0021] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0022] In these examples, parts and percentages are by mass unless otherwise indicated.
[0023] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0024] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0025] The present application provides a nickel-rich positive electrode material, including a core and a coating layer covering the core, wherein the core is doped with N element and cationic element, and the coating layer includes N element and cationic element; the general chemical formula of the nickel-rich positive electrode material is LiNi x Co y Mn z Al 1-x-y-z C c D d N n O2; wherein 0.80≤x≤0.95, x can be, for example, 0.80, 0.85, 0.86, 0.88, 0.90, 0.91, 0.92, 0.93, 0.95 or any value between 0.80 and 0.95; 0≤y≤0.10, 0≤z≤0.10, y and z can be, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any value between 0 and 0.10; C is a cationic element doped with the core, 0.10≤c≤0.30, c can be, for example, 0.10, 0.12, 0.15, 0.17, 0.18, 0.19, 0.20, 0.22, 0.25, 0.27, 0.30 or any value between 0.10 and 0.30; D is a cationic element in the coating layer, 0.10≤d≤0.20, d can be, for example, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20 or any value between 0.10 and 0.20; n≤0.45, n can be, for example, 0.1, 0.2, 0.3, 0.40, 0.45 or any value ≤0.45; wherein c, d and n are all mass percentage contents.
[0026] The nickel-rich positive electrode material provided in the present application adopts an anion-cation coupling co-doping strategy. The doping of N element in the anion can improve the atomic vacancies generated during the sintering process, and rearrange the charges in the unit cell structure by increasing the vacancy concentration of the electron position in the energy level band gap, adjusting the ratio of Ni elements with different valence states in the nickel-rich positive electrode material, and improving Ni 3+ The proportion of Ni 2+ By increasing the spacing between the unit cell layers, the primary particles can be regulated to increase the particle density and growth consistency, thus broadening the Li + transmission channel, stabilize the cell structure, increase Ni 2+ The migration energy barrier and the escape energy barrier of O2 can improve the lithium ion diffusion coefficient and kinetic performance, and slow down the drastic change of volume stress inside the primary particles of the material. In addition, after the introduction of cations into the material, the internal charge can be balanced by adjusting the ratio of anions and cations, and the Ni 2+ / Ni3+ ratio, so that the material can achieve the optimal Li / Ni mixed state and improve the electrochemical performance of the material.
[0027] The nickel-rich positive electrode material provided in the present application constructs a high-entropy material surface-low-entropy material interior dual-phase state by co-coating of N elements and cationic metal elements on the surface, utilizes the high-entropy shielding effect to reduce the dissolution of transition metals, inhibits the catalytic effect of transition metals on the electrolyte, improves the structural stability of the CEI film, slows down the epitaxial growth of the CEI film, stabilizes the median voltage, and effectively reduces the interface impedance of the positive electrode material.
[0028] In some embodiments, the cationic element doped with the core includes at least one of Zr, Sr, Y, Al, B, Mg, Nb, and Mo; The cationic element in the coating layer includes at least one of Al, W, Ti, Ce, Co, Ta, and Er.
[0029] In some embodiments, the thickness of the coating layer is 1~3nm, for example, it can be 1nm, 1.5nm, 2nm, 2.5nm, 3nm or any value between 1~3nm; the D50 of the nickel-rich positive electrode material is 9.0μm~13.5μm, for example, it can be 9.0μm, 9.5μm, 10.0μm, 10.5μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm or any value between 9.0μm~13.5μm.
[0030] In some embodiments, the specific surface area of the nickel-rich positive electrode material is 0.25-0.80 m 2 / g, for example, 0.25m 2 / g, 0.30m 2 / g, 0.35m 2 / g, 0.40m 2 / g, 0.45m 2 / g, 0.50m 2 / g, 0.55m 2 / g, 0.60m 2 / g, 0.65m 2 / g, 0.70m 2 / g, 0.75m 2 / g, 0.80m 2 / g or 0.25~0.80m 2 Any value between / g.
[0031] In some embodiments, the tap density of the nickel-rich cathode material is ≥ 2.2 g / cm 3 , for example, it can be 2.2 g / cm 3, 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 or ≥2.2 g / cm 3 Optionally, the tap density of the nickel-rich positive electrode material is 2.2-2.8 g / cm 3 .
[0032] In some embodiments, the 003 / 104 diffraction peak intensity ratio in the XRD characteristic peak of the nickel-rich positive electrode material is ≥1.30. Optionally, the 003 / 104 diffraction peak intensity ratio in the XRD characteristic peak of the nickel-rich positive electrode material is 1.30~1.45, for example, it can be 1.30, 1.33, 1.35, 1.39, 1.41, 1.43, 1.45 or any value between 1.30~1.45.
[0033] In some embodiments, the nickel-rich positive electrode material is a spherical secondary particle composed of stacked primary particles; the length of the primary particle is 300~500nm, and the length can be, for example, 300nm, 350nm, 400nm, 450nm, 500nm or any value between 300~500nm; the aspect ratio of the primary particle is between 1.5~3.0, and the aspect ratio can be, for example, 1.5, 2.0, 2.5, 3.0 or any value between 1.5~3.0.
[0034] The present application also provides a method for preparing the above-mentioned nickel-rich positive electrode material, please refer to Fig.14 ,include: S100: performing a first mixing of a nickel-rich positive electrode material precursor and a lithium source, and adding a first dual-phase coupling initiator during the first mixing process to obtain a first mixture; S200: performing a first sintering on the first mixture to obtain a material to be coated; S300: performing a second mixing on the material to be coated, and adding a second dual-phase coupling initiator during the second mixing process to obtain a second mixture; S400: performing a second sintering on the second mixture to obtain a nickel-rich positive electrode material.
[0035] Wherein, the first two-phase coupling initiator and the second two-phase coupling initiator both include anion elements and cation elements, and the anion element is N.
[0036] In some embodiments, step S100 first mixes a nickel-rich positive electrode material precursor and a lithium source, and adds a first dual-phase coupling initiator during the first mixing process, including: During the first mixing process of the nickel-rich positive electrode material precursor and the lithium source, the first two-phase coupling initiator after ultrasonic atomization is sprayed in, and microwave drying is performed to obtain a first mixture.
[0037] In some embodiments, step S300 performs a second mixing of the material to be coated and adds a second dual-phase coupling initiator during the second mixing process, including: During the second mixing process of the material to be coated, the second dual-phase coupling initiator after ultrasonic atomization is sprayed in, and microwave drying is performed to obtain a second mixture.
[0038] In order to avoid the problem of poor kinetics in gas-solid two-phase reactions, the preparation method of the nickel-rich positive electrode material provided in the present application provides a strategy of ultrasonic atomization and microwave radiation-assisted drying to introduce a two-phase coupling initiator into the interior and surface of the primary particles of the positive electrode material in the form of liquid-solid dispersion. The low-entropy phase elements inside are evenly distributed, and the orientation of the primary particles is consistent, which greatly alleviates the damage of the volume anisotropic stress to the interior of the material. The high-entropy phase limits the surface reconstruction, slows down the dissolution of elements and the erosion of harmful substances, and utilizes two-phase coupling to improve the various properties of the nickel-rich positive electrode material.
[0039] In some embodiments, the first mixing in step S100 and the second mixing in step S300 both include the following stages: a first stage, a second stage, and a third stage, wherein the mixing speed increases in sequence. The speed in the first stage is 50-400 r / min, for example, 50 r / min, 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, or any value between 50-400 r / min, and the time is 1-5 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, or any value between 1-5 min. The speed of the second stage is 100-600r / min, for example, it can be 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min or any value between 100-600r / min, and the time is 2-10min, for example, it can be 2min, 3min, 5min, 8min, 10min or any value between 2-10min. The speed of the third stage is 400-1000r / min, for example, it can be 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min or any value between 400-1000r / min, and the time is 10-20min, for example, it can be 10min, 12min, 13min, 15min, 17min, 18min, 20min or any value between 10-20min.
[0040] In some embodiments, the first two-phase coupled initiator after ultrasonic atomization and the second two-phase coupled initiator after ultrasonic atomization are both sprayed in the second stage, and the first two-phase coupled initiator and the second two-phase coupled initiator can be ultrasonically atomized by being dissolved in a solvent; and the spraying rate is 10-50mL / min, for example, it can be 10mL / min, 20mL / min, 30mL / min, 40mL / min, 50mL / min or any value between 10-50mL / min.
[0041] In some embodiments, microwave drying is performed in the third stage, and microwave drying can evaporate the solvents of the first two-phase coupling initiator and the second two-phase coupling initiator to prevent the materials from being wet and agglomerated and affecting subsequent steps. The power of microwave drying is 8-15 kW and the temperature is 50-80°C.
[0042] In some embodiments, based on the mass of the nickel-rich positive electrode material precursor, the amount of the first two-phase coupling initiator added is 1000-3000ppm, for example, it can be 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 2000ppm, 2200ppm, 2500ppm, 2700ppm, 3000ppm or any value between 1000-3000ppm.
[0043] In some embodiments, based on the mass of the material to be coated, the amount of the second dual-phase coupling initiator added is 1000-2000 ppm, for example, it can be 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm or any value between 1000-2000 ppm.
[0044] In some embodiments, the first two-phase coupled initiator and the second two-phase coupled initiator are both secondary particles composed of primary particles, the particle size of the primary particles is ≤30 nm, and the particle size of the secondary particles is 1 μm to 3 μm.
[0045] In some embodiments, the cationic element of the first dual-phase coupling initiator includes at least one of Zr, Sr, Y, Al, B, Mg, Nb, and Mo; the cationic element of the second dual-phase coupling initiator includes at least one of Al, W, Ti, Ce, Co, Ta, and Er.
[0046] In some embodiments, the first sintering in step S200 includes: continuously introducing oxygen, heating from room temperature to 450°C at a heating rate of 5°C / min and keeping warm for 2 hours, then heating to 600°C at a heating rate of 1°C / min and keeping warm for 2 hours, and then heating to 700-800°C at a heating rate of 2°C / min and keeping warm for 10-15 hours.
[0047] In some embodiments, the second sintering in step S400 includes: heating from room temperature to 500-700° C. at a heating rate of 2° C. / min and maintaining the temperature for 6-12 hours.
[0048] In some embodiments, the chemical formula of the nickel-rich cathode material precursor is: Ni x Co y Mn z Al 1-x-y-z (OH)2, where 0.80≤x≤0.95, 0≤y≤0.10, 0≤z≤0.10.
[0049] In some embodiments, the particle size D50 of the lithium source is 1 μm to 5 μm. The lithium source is selected from any one of LiOH, Li2CO3, CH3COOLi, and Li2C2O4.
[0050] The present application also provides a positive electrode plate, comprising the above-mentioned nickel-rich positive electrode material.
[0051] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0052] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0053] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0054] Example 1 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.37kg of lithium hydroxide and 5kg of nickel-rich precursor Ni were added in a ratio of 1.045:1.0 (molar ratio). 0.90 Mn 0.10 (OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0055] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln for sintering by introducing oxygen (≥90%). The temperature is set to rise and fall in a program, and the final constant temperature section is set to 735°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0056] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0057] After the mixing is completed, the material is transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the material is cooled to room temperature with the furnace to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 1. 0.90 Mn 0.10 B 0.25 Ce 0.15 N 0.35 Among them, in the CeN with a coating amount of 1500ppm, the coating amount of N element is about 100ppm, which is basically undetectable. Therefore, the amount of N element in the positive electrode material is basically the doping amount in the core, and the following embodiments are similar to the comparative examples.
[0058] Example 2 53g of nano-biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.35kg of lithium hydroxide and 5kg of nickel-rich precursor Ni 0.88 Co 0.09 Al 0.03 (OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0059] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln for sintering by introducing oxygen (≥95%). The temperature is set to rise and fall in a program, and the final constant temperature section is set to 725°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0060] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0061] After the mixing is completed, the materials are transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the furnace is cooled to room temperature to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 2. 0.88 Co 0.09 Al 0.03 B 0.25 Ce 0. 15 N 0.35 O2.
[0062] Example 3 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.38kg of lithium hydroxide and 5kg of nickel-rich precursor Ni were mixed in a ratio of 1.05:1.0 (molar ratio). 0.85 Co 0.10 Mn 0.05 (OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0063] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln for sintering by introducing oxygen (≥90%). The temperature is set to rise and fall in a program, and the final constant temperature section is set at 760°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0064] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0065] After the mixing is completed, the material is transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the material is cooled to room temperature with the furnace to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 3. 0.85 Co 0.10 Al 0.05 B 0.25 Ce 0.15 N 0.35 O2.
[0066] Example 4 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.35kg of lithium hydroxide and 5kg of nickel-rich precursor Ni 0.90 Co 0.06 Mn 0.04(OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0067] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln to be sintered by introducing oxygen (≥95%). The temperature is set to rise and fall by a program, and the final constant temperature section is set to 750°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0068] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0069] After the mixing is completed, the material is transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the material is cooled to room temperature with the furnace to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 4. 0.90 Co 0.06 Mn 0.04 B 0.25 Ce 0.15 N 0.35 O2.
[0070] Example 5 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.38kg of lithium hydroxide and 5kg of nickel-rich precursor Ni were added in a ratio of 1.045:1.0 (molar ratio). 0.92 Co 0.03 Mn 0.03 Al 0.02 (OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0071] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln for sintering by introducing oxygen (≥95%). The temperature is set to rise and fall in a program, and the final constant temperature section is set to 725°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0072] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0073] After the mixing is completed, the material is transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the furnace is cooled to room temperature to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 5. 0.92 Co 0.03 Mn 0.03 Al 0.02 B 0.25 Ce 0.15 N 0.35 O2.
[0074] Example 6 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.36kg of lithium hydroxide and 5kg of nickel-rich precursor Ni 0.95 Co 0.02 Mn 0.02 Al 0.01 (OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0075] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln for sintering by introducing oxygen (≥99%). The temperature is set to rise and fall in a program, and the final constant temperature section is set at 715°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0076] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0077] After the mixing is completed, the materials are transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the furnace is cooled to room temperature to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 6. 0.95 Co 0.02 Mn 0.02 Al 0.01 B 0.25 Ce 0.15 N 0.35 O2.
[0078] Example 7 According to the ratio of 1.04:1.0 (molar ratio), 2.35kg lithium hydroxide and 5kg nickel-rich precursor Ni 0.90 Co 0.06 Mn 0.04 (OH)2 and 53 g of nano dual-phase coupling initiator N2H4BH3 (2500 ppm) were added into a high-speed mixer and mixed according to the procedure.
[0079] After the mixing is completed, the material is released, loaded into a sagger, transferred to a kiln, and sintered with oxygen (≥95%). The temperature is set to rise and fall in a program, and the final constant temperature section is set to 750°C. After the constant temperature sintering is completed, the oxygen is stopped and N2 is introduced. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged to obtain the material to be coated.
[0080] 10g of nano dual-phase coupling initiator CeN (1500ppm) and 5kg of the material to be coated are put into a high-speed mixer and mixed according to the program. After the mixing is completed, the mixed material is transferred to a kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the furnace is cooled to room temperature to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 7. 0.90 Co 0.06 Mn 0.04 B 0. 25 Ce 0.15 N 0.35 O2.
[0081] Example 8 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.35kg of lithium hydroxide and 5kg of nickel-rich precursor Ni 0.90 Co 0.06 Mn 0.04(OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0082] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln to be sintered by introducing oxygen (≥95%). The temperature is set to rise and fall by a program, and the final constant temperature section is set to 750°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0083] Take 8g of nano two-phase coupling initiator W2N (1500ppm) and 24g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material C to be coated at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0084] After the mixing is completed, the materials are transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 650°C. After the insulation is completed, the furnace is cooled to room temperature to obtain the positive electrode material LiNi modified by the anion-cation dual-phase coupling of Example 8. 0.90 Co 0.06 Mn 0.04 B 0.25 W 0.15 N 0.35 O2.
[0085] Comparative Example 1 71g H3BO3 (2500ppm) and 213g deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.35kg lithium hydroxide and 5kg nickel-rich precursor Ni were dispersed and mixed in a ratio of 1.04:1.0 (molar ratio) to obtain a mixed solution A. 0.90 Co 0.06 Mn 0.04 (OH)2 was added into a high-speed mixer for mixing. The mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0086] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln to be sintered by introducing oxygen (≥95%). The temperature is set to rise and fall by a program, and the final constant temperature section is set to 750°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the material C to be coated.
[0087] Take 10g of nano dual-phase coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution D. Spray the mixed solution D into 5kg of the material to be coated C at the same rate in the medium speed stage, and the subsequent mixing process is the same as the raw material mixing process.
[0088] After the mixing is completed, the materials are transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the materials are cooled to room temperature with the furnace to obtain the doped, coated and modified positive electrode material LiNi of Comparative Example 1. 0.90 Co 0.06 Mn 0.04 B 0. 25 Ce 0.15 O2.
[0089] Comparative Example 2 2.35 kg of lithium hydroxide and 5 kg of nickel-rich precursor Ni were mixed in a ratio of 1.04:1.0 (molar ratio). 0.90 Co 0.06 Mn 0.04 Add (OH)2 into the high-speed mixer and mix according to the procedure. After the mixture is mixed, release the mixture and put it into a sagger, transfer it into a kiln and introduce oxygen (≥95%) for sintering. Set the temperature rise and fall program, and finally set the temperature of the constant temperature section to 750℃. After the constant temperature sintering is completed, stop introducing oxygen and switch to introducing N2. After cooling to room temperature, take out the material, crush it, wash it with water, and centrifuge it to obtain the material to be coated.
[0090] Take 10g of nano-duplex coupling initiator CeN (1500ppm) and 30g of deionized water in a ratio of 1:3 (mass ratio) and disperse and mix them to obtain a mixed solution. Spray the mixed solution into 5kg of the material to be coated at a rate of 20mL / min in the medium-speed stage. After the medium-speed mixing stage, enter the high-speed mixing stage and start microwave radiation drying at the same time.
[0091] After the mixing is completed, the material is discharged and transferred to the kiln, and the temperature is set to rise and fall while oxygen (≥90%) is introduced for sintering. The constant temperature is set to 680°C. After the insulation is completed, the furnace is cooled to room temperature to obtain the coated modified positive electrode material LiNi of Comparative Example 2. 0.90 Co 0.06 Mn 0.04 Ce 0.15 O2.
[0092] Comparative Example 3 2.35 kg of lithium hydroxide and 5 kg of nickel-rich precursor Ni were mixed in a ratio of 1.04:1.0 (molar ratio). 0.90 Co 0.06 Mn 0.04(OH)2 is added to the high-speed mixer and mixed according to the program. After the material is released, it is placed in a sagger and transferred to a kiln to introduce oxygen (≥95%) for sintering. The program is set to increase and decrease the temperature. The final constant temperature section is set to 750°C. After the constant temperature sintering is completed, stop introducing oxygen and switch to introducing N2. After cooling to room temperature, the material is taken out and crushed, washed with water, and centrifuged and dried to obtain the unmodified LiNi of Comparative Example 3. 0.90 Co 0.06 Mn 0.04 O2.
[0093] Comparative Example 4 53g of nano biphasic coupling initiator N2H4BH3 (2500ppm) and 159g of deionized water were dispersed and mixed in a ratio of 1:3 (mass ratio) to obtain a mixed solution A. 2.38kg of lithium hydroxide and 5kg of nickel-rich precursor Ni were added in a ratio of 1.045:1.0 (molar ratio). 0.92 Co 0.03 Mn 0.03 Al 0.02 (OH)2 was added to a high-speed mixer for mixing, and the mixed liquid A was ultrasonically atomized and sprayed into the mixed raw materials at a rate of 20 mL / min during the medium-speed mixing stage. After the medium-speed mixing stage, it was switched to the high-speed mixing stage, and microwave radiation drying was started at the same time to obtain material B.
[0094] After the mixing is completed, material B is released, loaded into a sagger and transferred into a kiln to be sintered by introducing oxygen (≥95%), and the program temperature is set to rise and fall, and the final constant temperature section is set to 725°C. After the constant temperature sintering is completed, the introduction of oxygen is stopped and switched to the introduction of N2. After cooling to room temperature, the material is taken out, crushed, washed and dried to obtain the LiNi of comparative example 4 which is only constructed by anion-cation dual-phase coupling for low-entropy internal core 0.90 Co 0.06 Mn 0.04 B 0.25 N 0.35 O2.
[0095] Figure 1 to Figure 7 The scanning electron microscope images of the positive electrode materials of Examples 1 to 7 are shown respectively. The nano-biphasic coupling initiators used in each example are N2H4BH3 and CeN. Figure 8This is a scanning electron microscope image of the positive electrode material of Example 8, the difference being that the nano-biphasic coupling initiator used to construct the high entropy phase surface is replaced with W2N on the basis of Example 4. The initiator is uniformly coated on the outer surface of the secondary particles through ultrasonic atomization and microwave radiation-assisted drying. Due to the difference in Ni content and morphology in the nickel-rich precursor, the primary particles of the nickel-rich positive electrode material finally generated are different, but the outer surface of the primary particles and the grain boundaries of the secondary spherical particles are covered by the coating layer, and the exposed area of the fresh phase interface is small, which effectively reduces the contact area between the material and the electrolyte, and effectively reduces the dissolution of transition metal elements and the occurrence of side reactions at the two-phase interface in electrochemical tests.
[0096] Example 7 is based on Example 4, but the ultrasonic atomization and microwave-assisted method are replaced by the commonly used high-mixer dry mixing method. Figure 7 It can be seen from the electron microscope that the disadvantage of traditional dry mixing in coating uniformity is very obvious. A fuzzy coating layer can be seen on the surface of the secondary particles, the coating effect on the surface of the primary particles is poor, and the grain boundary interface is more obviously exposed. In the electrochemical test, it is easy to be affected by side reactions and metal element dissolution, resulting in a decrease in electrochemical performance. Figure 9~Figure 12 The scanning electron microscope images of the positive electrode materials of comparative examples 1 to 4 are respectively shown. Comparative example 1 is based on example 4 and is doped with nano-boric acid for the first sintering. The coating still uses nano-initiator CeN and atomized microwave-assisted method. The overall coating effect in the electron microscope is basically the same as that in example 4. The coating layer is uniform. Fig. 9 Directly observed.
[0097] Comparative Example 2 removes the doping of nano-boric acid on the basis of Comparative Example 1, and only retains the atomized microwave-assisted coating of CeN. Therefore, the overall electron microscope morphology is basically consistent with Comparative Example 1 and Example 4, with no obvious difference.
[0098] Fig.11 It is a nickel-rich positive electrode material that has not been modified in any way. The surfaces and grain boundaries of its primary and secondary particles are clearly visible, and some primary particles have surface damage caused by processes such as crushing and water washing. Fig.12 The nickel-rich cathode material was constructed by a nano-biphasic coupling initiator only once for the low-entropy internal core. Since the high-entropy phase surface was not constructed, the electron microscopy and Fig.11 Similarly, some of the primary particles are broken.
[0099] In order to prove the electrochemical performance of the materials, the positive electrode materials of the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 4 were tested for the electrical performance of the relevant button batteries, and the specific process is as follows: (1) Take the positive electrode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 4, and weigh three materials in a ratio of 96 (positive electrode material): 2 (binder PVDF): 2 (conductive agent SP); (2) Add solvent NMP and disperse and mix evenly in a beaker to form a slurry, and then use a scraper to coat it on a conductive aluminum foil (surface density 20.0-22.0 mg / cm 2 ); (3) Place in a 120°C vacuum drying oven and dry for 2 hours, then cut into electrodes with a diameter of 14 mm, weigh them, and then vacuum bake at 120°C for 2 hours; (4) Assemble CR2025 button cells in a nitrogen glove box using lithium metal as the negative electrode; (5) Place the button cell into the Xinwei test system for charge and discharge testing at a constant temperature of 25°C.
[0100] In order to verify the effect of the initiator on the crystal structure and electrochemical performance, Table 1 lists the 0.1C first discharge capacity and 0.2C~2C rate discharge capacity of Examples 1 to 8 and Comparative Examples 1 to 4, as well as the 003 / 104 peak intensity ratio θ of Example 4, Example 7 and Comparative Examples 1 to 4. Fig.13 The first electrochemical charge-discharge curves of Example 4, Example 7 and Comparative Examples 1 to 4 are listed.
[0101] Table 1 Battery performance results of various embodiments and comparative examples
[0102] From Table 1 and Fig.13 It can be seen from the curve that Example 4, which is modified by atomization microwaves and completes two-phase coupling under the same chemical formula, has the best electrochemical performance compared with Comparative Examples 1 to 4, with a discharge capacity of 222 mAh / g at 0.1C and 188 mAh / g at 2C. Its crystal structure analysis shows that the 003 / 104 diffraction peak intensity ratio is 1.41. After replacing the two-phase coupling initiator for constructing a high entropy phase surface on the basis of Example 4, the electrochemical performance of Example 8 is basically at the same level as that of Example 4, proving that the method has good practicality and applicability.
[0103] Secondly, in Example 7, only the initiator is used to complete the two-phase coupling modification. Its 0.1C discharge capacity is 219 mAh / g, and the 2C discharge capacity is 184 mAh / g, which is slightly lost compared with Example 4. The reason may be that the high-speed mixer dry mixing is used. During the same-phase mixing process, the contact area between the initiator and the nickel-rich positive electrode precursor is small. Affected by the rotation speed and material viscosity during the mixing process, the actual amount of initiator participating in the two-phase coupling reaction is less than the designed amount. The crystal structure analysis results are not much different from those in Example 4. At a larger rate, the unit cell volume shrinks after Li is released, and the structure collapses, resulting in a decrease in capacity.
[0104] Comparative Example 1, based on Example 4, only carried out cation modification in the first high-temperature sintering stage. Its 0.1C discharge capacity was only 217 mAh / g, and its 2C discharge capacity was 175 mAh / g, proving that single cation modification cannot effectively complete atomic-level structural design and defect repair. Therefore, the 003 / 104 peak intensity ratio was reduced to 1.35. The loss of both the reversible specific capacity of the first charge and discharge and the rate discharge capacity was greater than the effect of the anion-cation coupling modification.
[0105] Comparative Example 2, based on Example 4, only completes the construction process of the high entropy phase on the initiator surface. There are many atomic defects and oxygen vacancies inside the structure, and the 003 / 104 peak intensity ratio is only 1.30. The reversible capacity loss is extremely large, the 0.1C first discharge capacity is only 213 mAh / g, and the 2C discharge capacity is reduced to 170 mAh / g.
[0106] The blank group of Comparative Example 3 is a nickel-rich material without any modification. The internal structure has serious Li / Ni mixing, many O vacancies, chaotic atomic arrangement, and the peak intensity ratio is further reduced to 1.25. The surface is severely damaged due to water washing, crushing, etc. The 0.1C discharge capacity is only 205mAh / g, and the 2C rate capacity is only 161mAh / g.
[0107] Comparative Example 4 only completes the construction process of the low entropy phase core of the initiator on the basis of Example 4. The internal structure is stable. Crystal structure analysis shows that the 003 / 104 diffraction peak intensity ratio is similar to that of Example 4, but the high entropy phase is not constructed on the surface. The crushing and water washing damage the surface of the material, so the ionic and electronic conductivity is affected to a certain extent. The 0.1C discharge capacity is 214 mAh / g, and the 2C rate capacity is 169 mAh / g, which is similar to Comparative Example 2.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0109] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A nickel-rich positive electrode material, characterized in that: The nickel-rich positive electrode material comprises a core and a coating layer covering the core, wherein the core is doped with N element and cationic element, and the coating layer comprises N element and cationic element; the general chemical formula of the nickel-rich positive electrode material is LiNi x Co y Mn z Al 1-x-y-z C c D d N n O2; wherein, 0.80≤x≤0.95, 0≤y≤0.10, 0≤z≤0.10, C is the cationic element doped in the core, 0.10≤c≤0.30, D is the cationic element in the coating layer, 0.10≤d≤0.20, and n≤0.
45.
2. The nickel-rich positive electrode material according to claim 1, characterized in that The cationic element doped in the core includes at least one of Zr, Sr, Y, Al, B, Mg, Nb, and Mo; The cationic element in the coating layer includes at least one of Al, W, Ti, Ce, Co, Ta, and Er.
3. The nickel-rich positive electrode material according to claim 1 or 2, characterized in that: At least one of the following conditions is met: (1) The thickness of the coating layer is 1-3 nm; (2) The D50 of the nickel-rich positive electrode material is 9.0 μm to 13.5 μm; (3) The specific surface area of the nickel-rich positive electrode material is 0.25~0.80m 2 / g; (4) The tap density of the nickel-rich positive electrode material is ≥ 2.2 g / cm 3 ; (5) The 003 / 104 diffraction peak intensity ratio in the XRD characteristic peak of the nickel-rich positive electrode material is ≥1.30; (6) The nickel-rich positive electrode material is a spherical secondary particle composed of stacked primary particles; (7) When condition (6) is met, the length of the primary particle is 300-500 nm; (8) When condition (6) is met, the aspect ratio of the primary particles is between 1.5 and 3.
0.
4. A method for preparing a nickel-rich positive electrode material, characterized in that: include: A nickel-rich positive electrode material precursor and a lithium source are first mixed, and a first two-phase coupling initiator is added during the first mixing process to obtain a first mixture; Performing a first sintering on the first mixture to obtain a material to be coated; Performing a second mixing on the material to be coated, and adding a second dual-phase coupling initiator during the second mixing process to obtain a second mixture; Performing a second sintering on the second mixture to obtain the nickel-rich positive electrode material; Wherein, the first dual-phase coupling initiator and the second dual-phase coupling initiator both include anion elements and cation elements, and the anion element is N.
5. The method for preparing a nickel-rich positive electrode material according to claim 4, characterized in that: The first step of mixing the nickel-rich positive electrode material precursor and the lithium source and adding the first dual-phase coupling initiator during the first mixing process includes: During the first mixing process of the nickel-rich positive electrode material precursor and the lithium source, the first two-phase coupling initiator after ultrasonic atomization is sprayed, and microwave drying is performed to obtain the first mixture; And / or, the second mixing of the material to be coated and the addition of a second dual-phase coupling initiator during the second mixing process comprises: During the second mixing process of the material to be coated, the second dual-phase coupling initiator after ultrasonic atomization is sprayed in, and microwave drying is performed to obtain the second mixture.
6. The method for preparing a nickel-rich positive electrode material according to claim 5, characterized in that: The first mixing process and the second mixing process both include: a first stage, a second stage, and a third stage in which the mixing speed increases in sequence; and meet at least one of the following conditions: A. The speed of the first stage is 50-400r / min, and the time is 1-5min; B. The speed of the second stage is 100-600r / min, and the time is 2-10min; C. The rotation speed of the third stage is 400-1000r / min, and the time is 10-20min; D. the first two-phase coupled initiator after ultrasonic atomization and the second two-phase coupled initiator after ultrasonic atomization are both sprayed in the second stage; E. The injection rate of the first two-phase coupling initiator after ultrasonic atomization and the second two-phase coupling initiator after ultrasonic atomization is 10-50 mL / min; F. the microwave drying is carried out in the third stage; G. The power of the microwave drying is 8-15 kW and the temperature is 50-80°C.
7. The method for preparing a nickel-rich positive electrode material according to any one of claims 4 to 6, characterized in that: At least one of the following conditions is met: A. Based on the mass of the nickel-rich positive electrode material precursor, the amount of the first dual-phase coupling initiator added is 1000-3000ppm; B. Based on the mass of the material to be coated, the amount of the second dual-phase coupling initiator added is 1000-2000ppm; C. The first two-phase coupled initiator and the second two-phase coupled initiator are both secondary particles composed of primary particles, the particle size of the primary particles is ≤30nm, and the particle size of the secondary particles is 1μm~3μm; D. The cationic element of the first dual-phase coupling initiator includes at least one of Zr, Sr, Y, Al, B, Mg, Nb, and Mo; the cationic element of the second dual-phase coupling initiator includes at least one of Al, W, Ti, Ce, Co, Ta, and Er; E. The first sintering comprises: continuously introducing oxygen, heating from room temperature to 450°C at a heating rate of 5°C / min and keeping the temperature for 2 hours, then heating to 600°C at a heating rate of 1°C / min and keeping the temperature for 2 hours, then heating to 700-800°C at a heating rate of 2°C / min and keeping the temperature for 10-15 hours; F. The second sintering includes: heating from room temperature to 500-700°C at a heating rate of 2°C / min and keeping the temperature for 6-12h; G. The chemical formula of the nickel-rich positive electrode material precursor is: Ni x Co y Mn z Al 1-x-y-z (OH)2, where 0.80≤x≤0.95, 0≤y≤0.10, 0≤z≤0.10; H. The particle size D50 of the lithium source is 1 μm to 5 μm; I. The lithium source is selected from any one of LiOH, Li2CO3, CH3COOLi, and Li2C2O4.
8. A positive electrode sheet, characterized in that: The nickel-rich positive electrode material comprises the nickel-rich positive electrode material according to any one of claims 1 to 3.
9. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 8.
10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Lithium ion battery cathode multicomponent material and preparation method thereof
CN104319386A
Preparation method of positive electrode material for high-power lithium ion battery
CN110931772A
High-nickel ternary positive electrode material with single crystal morphology and preparation method of high-nickel ternary positive electrode material
CN111463411A
Nickel-rich ternary positive electrode material and preparation method and application thereof
CN114988492A
Ternary positive electrode material as well as preparation method and application thereof
CN115275195A